Transactional e-health literacy and its association with e-health services use in Polish adults: a cross-sectional study - Paulina Smoła; Urszula Zwierczyk; Mariusz Duplaga (Frontiers Media S.A., 2024)
IntroductionThe transactional model of e-health literacy addresses not only the skills needed for handling online health-related information but also the capacity to communicate regarding health issues on the Internet. It also emphasizes a critical component of e-health literacy: enabling appraisal and selection of information adequate to individual needs. Our study aimed to culturally adapt the instrument assessingTransactional e-Health Literacy (TeHL) and examine the association between TeHL and the use of e-health services by Polish adult Internet users.MethodsThe analysis was conducted on data from an online survey among 1,661 respondents. After cultural adaptation and piloting of the Polish version of the instrument measuring TeHL, exploratory and confirmatory factor analyses were performed on two samples obtained by random splitting of the original data set. The roles of TeHL categories in the use of several types of e-health services were assessed with multivariable logistic regression models.ResultsWe have found that the four-factor model of the Polish version of the TeHL instrument, consisting of 17 items, obtained after excluding item 13, shows the best fit to the measurement data (NFI = 0.950, RFI 0.938, TLI = 0.951, CFI = 0.960, GFI = 0.932, RMSEA = 0.066). Regression modeling revealed that Functional e-health literacy is a significant positive predictor of the use of remote physician advice, the Internet Patient Account Portal, portals providing general health-related information, and websites allowing for checking laboratory test results. Communicative eHL was significantly negatively related to the use of general health-related information portals and positively related to the use of portals offering paid medical advice. Critical e-health literacy was a significant negative predictor of the use of remote physician advice and the laboratory test results websites but a positive predictor of using portals offering paid medical advice and websites offering easy access to e-prescriptions. Finally, Translational e-health literacy was significantly positively associated with the use of the Internet Patient Account Portal, general health-related information portals, and laboratory test results websites.DiscussionPolish version of the instrument assessing TeHL is a tool of confirmed validity that can be used for e-health research in Poland. The relationships between four types of TeHL and the use of concrete e-health solutions show a complex pattern requiring further evaluation.